Effectiveness of spinal cord stimulation in diabetic patients with chronic limb-threatening ischemia: small cohort study - Cyrek, Anna E.; Koch, Dietrich; Pacha, Arkadius; Radunz, Sonia (Frontiers in Surgery, 2024)
BackgroundChronic limb-threatening ischemia (CLTI) is the most severe form of peripheral artery disease (PAD). Patients with diabetes mellitus (DM) have a faster progression of PAD and a fourfold increased risk of CLTI compared to patients without DM. Epidural spinal cord stimulation (SCS) has been used as a method to improve microcirculation, relieve ischemic pain and reduce the number of amputations in patients with PAD. This is a retrospective small cohort analysis of patients with diabetes and the long-term treatment effect of spinal cord stimulation.MethodsAs the main outcome of the study, we evaluated the survival and amputation of 13 diabetic patients with chronic lower-limb ischemia who were not eligible for surgical or interventional therapy. Secondary outcomes included ankle-brachial index (ABI), ischemic pain intensity, quality of life, use of analgesic medications and skin wound outcomes analyzed during long-term follow-up.ResultsBetween January 2010 and January 2017, 13 patients underwent SCS implantation in our vascular center. At 1-year follow-up, the limb salvage rate was 92.3% (12 of 13 patients), and limb ulcers healed in 75% of patients (6/8). No patient died during the one-year follow-up. A total of 4 of patients (31%) experienced major amputation during long-term follow-up, all of them were Fontaine stage IV. Pain intensity and quality of life improved significantly at 6-month follow-up (p < 0.05). ABI measurements were unaffected by SCS treatment. There were no complications related to the procedure or device.ConclusionsSCS is a promising treatment option for diabetic patients unsuitable for endovascular or surgical revascularization. The method improves limb survival in diabetic patients with critical limb ischemia, provides significant pain control, and improves patients' quality of life. However, more studies are needed to clarify the indications for SCS and clarify its effects on the vascular system.